2009
DOI: 10.1116/1.3179162
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electron temperatures and electron energy distribution functions in dual frequency capacitively coupled CF4/O2 plasmas using trace rare gases optical emission spectroscopy

Abstract: Measurements of electron temperatures ͑T e ͒ and electron energy distribution functions ͑EEDFs͒ in a dual frequency capacitively coupled etcher were performed by using trace rare gas optical emission spectroscopy ͑TRG-OES͒. The parallel plate etcher was powered by a high frequency ͑60 MHz͒ "source" top electrode and a low frequency ͑13.56 MHz͒ "substrate" bottom electrode. T e first increased with pressure up to ϳ20 mTorr and then decreased at higher pressures. Increasing the bottom rf power resulted in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
(34 reference statements)
5
13
1
Order By: Relevance
“…The evolution of EEPFs in this paper is quite different from the results of the approximate EEDFs in an 80%CF 4 þ 20%O 2 plasma (60/13.56 MHz DF-CCP) 10 which were obtained by TRG-OES. The results given by Chen et al 10 showed that the EEDF exhibited a bi-Maxwellian character with an enhanced high energy tail, especially above 20 mTorr, while the Druyvesteyn distribution was obtained at high pressure in this paper. This partly could be due to the different chemical characterization of CF 4 /O 2 and argon gas.…”
Section: -3contrasting
confidence: 95%
See 2 more Smart Citations
“…The evolution of EEPFs in this paper is quite different from the results of the approximate EEDFs in an 80%CF 4 þ 20%O 2 plasma (60/13.56 MHz DF-CCP) 10 which were obtained by TRG-OES. The results given by Chen et al 10 showed that the EEDF exhibited a bi-Maxwellian character with an enhanced high energy tail, especially above 20 mTorr, while the Druyvesteyn distribution was obtained at high pressure in this paper. This partly could be due to the different chemical characterization of CF 4 /O 2 and argon gas.…”
Section: -3contrasting
confidence: 95%
“…This partly could be due to the different chemical characterization of CF 4 /O 2 and argon gas. However, it is hard to compare the EEDFs obtained by Chen et al 10 and that in this paper. One reason is that the measuring of EEDFs is different: the Langmuir probe technique was used in this paper, while TRG-OES technique was used by Chen et al, 10 so, only the approximate EEDFs were obtained by them.…”
Section: -3mentioning
confidence: 67%
See 1 more Smart Citation
“…If we assume that the atomic fluorine density directly depends on I(F), this shows that a relationship exists between the density of the atomic fluorine and the SiN :H etch rate. In fact, a number of recent studies have produced similar results to utilize a relation between the OES intensity and plasma density [26][27][28].…”
Section: Discussion When Sin :H Film Is Etched Using Fluorinebased Gmentioning
confidence: 90%
“…For control of the plasma characteristics as required for nanoscale semiconductor device processing, various plasma sources including capacitively coupled plasma (CCP) sources and inductively coupled plasma (ICP) sources have been widely investigated. [1][2][3][4][5][6] CCP sources are known to have excellent plasma uniformity while having low plasma density of about a few 10 10 /cm 3 , in addition to low gas dissociation characteristics. In contrast, ICP sources are known to have less plasma uniformity while having high plasma density, which is above 10 11 /cm 3 , along with high gas dissociation characteristics.…”
Section: Introductionmentioning
confidence: 99%